A quantitative ultrastructural study of the liver and the spleen in fatal falciparum malaria. - Prommano, O; Chaisri, U; Turner, G; Wilairatana, P; Ferguson, D; Viriyavejakul, P; White, N; Pongponratn, E (2005)
We performed a retrospective study of 25 patients who died of severe falciparum malaria in Thailand and Vietnam using electron microscopy. The aims of the study were: to determine if there was any significant association between parasitized red blood cells (PRBC) sequestered in liver and spleen and particular pre-mortem clinical complications, and to compare the degree of parasite load between the liver and spleen within the same patients. PRBC sequestrations in each organ were compared with the pre-mortem parasitemia, to calculate the sequestration index (S.I.). The S.I. showed that the degree of PRBC sequestration in the spleen was higher than the liver (S.I. median = 3.13, 0.87, respectively) (p < 0.05). The results of quantitative ultrastructural study showed a significantly high parasite load in the liver of patients with jaundice, hepatomegaly and liver enzyme elevation (p < 0.05). We found a significant correlation between PRBC sequestration in the liver and a high serum bilirubin level, a high aspartate aminotransferase (AST) level and an increase in the size of the liver (Spearman's correlation coefficient = 0.688, 0.572, 0.736, respectively). Furthermore, a higher parasite load was found in the liver of patients with acute renal failure (ARF) compared to patients without ARF (p < 0.05). These findings suggest that PRBC sequestration in the liver is quantitatively associated with pre-mortem hepatic dysfunction and renal impairment. There was no significant difference between splenomegaly and PRBC sequestration. The size of a palpable spleen was not correlated with parasite load in the spleen. When ultrastructural features were compared between the two reticuloendothelial organs, we found that the spleen had more PRBC and phagocytes than the liver. The spleen of non-cerebral malaria (NCM) patients had more phagocytes than cerebral malaria (CM) patients. This observation reveals that the spleen plays a major role in malaria parasite clearance, and is associated with host defence mechanisms against malaria.